Effects of passage number on growth and productivity of hybridoma secreting MRSA anti-PBP2a monoclonal antibodies - Corrêa, Arthur Luiz (Cytotechnology, 2015)
Monoclonal antibodies (mAb) are high added value glycoproteins recommended for immunotherapy, diagnosis, and also for the treatment of bacterial infections resistant to multiple drugs such as Methicillin Resistant Staphylococcus aureus (MRSA). In addition to environmental conditions related to cell cultures, the intrinsic characteristics of hybridoma cells, like the secretion stability of monoclonal antibodies by the cells through successive subcultures, are relevant for the characterization of cell lines related to the productivity of mAb. The rate of mAb production differs significantly between different cell lines and different passage numbers, and it is an important variable in characterization of cell lines. In order to find a more robust, faster-growing, and higher-productivity cell line of hybridoma, cultivations in 24-well plates were performed in different subculture periods, or cell passages (P), of hybridoma cells producing MRSA anti-PBP2a monoclonal antibodies [MRSA-antiPBP2a (mAb)]. The objective of this study was to study the effects of cell growth and production of MRSA-antiPBP2a mAb secreted by murine hybridoma cells grown in different passages as well as determine the which passages the hybridomas can be cultivated without harming their growth and productivity. So, cell growth profiles of hybridomas secreting MRSA-antiPBP2a (mAb) and the production of MRSA-antiPBP2a mAb in different subculture periods or cell passages (P) were studied. Cell growth tests, monoclonal antibody productivity, and metabolite characteristics revealed substantial differences in those cells kept between P10 and P50. Similarities in the secretion of monoclonal antibody, growth, and metabolic profiles, were noted in the MRSA-antiPBP2a mAb producing hybridoma cells kept between P10 and P20. Also, glucose consumption (g/L) and lactate production (g/L) in the latter cell cultures were monitored daily through biochemical analyzer. As of P30, it was observed a 4.4 times reduction in productivity, a 13 % reduction in metabolic yield, and a significant change in cell growth. Secretion of MRSA-antiPBP2a mAb should be obtained through the culture of hybridomas up to P20 in order to keep its stability.